Perfil epidemiológico de recém-nascidos com anomalias congênitas no Hospital Universitário Júlio Müller, Mato Grosso, Brasil - Figueiredo, Glaucia Maria Duarte Preza (2018)
Congenital anomaly (CA) is a functional or structural anomaly of fetal development due to a factor that originates before birth, whether genetic, environmental or unknown, even when the defect is not apparent in the newborn and only manifests itself later. About 60% of ACs do not have a known origin and 40% are of genetic, environmental or combination of both. Around 2 to 5% of newborns in Brazil and in the world have some type of CA. There are several CA study organizations in the world, including the Latin American Collaborative Study Network on Congenital Malformations (ECLAMC), to which Brazil is a part. Brazil does not have a specific system of registration of CAs and works have shown an underreporting of CAs based only on filling in the Declarations of Live Births (DNV). Anomalies play an important role in morbidity and are the second leading cause of infant mortality. The present study has as goal to identify the incidence, the epidemiological profile of the newborn alive with CA, as well as the quality of DNV filling at the Júlio Müller University Hospital, located in Cuiabá-MT, a reference in high-risk pregnancies that treats the entire State. This is a prospective descriptive cross-sectional study where the number of births in a one-year period was identified and newborns with CA were analyzed. The incidence of CA found was 3.62% (39 cases). In 22 cases (56.41%) the etiology of CA was not identified, with congenital infections in 10 cases (25.64%) and genetic syndromes in 7 (17.95%). Of the 39 NBs with CA, 21 had an association of one or more abnormalities. The CAs were predominant in NB children of mothers under 35 years (84.18%) and with up to three pregnancies (74.35%). Among infants with AC, 58% weighed below 2,500 grams (low weight), 23 (59%) were born preterm and 16 (41%) were term. The delivery was caesarean section in 84, 6% of the cases. It was found 22 (58,4%) female NBs and 17 (43,6%) males were observed. The organs most affected with CA were respectively skull, face and related structures, central nervous system, heart, digestive system and limbs. In 33.3% of the cases, the DNV was not adequately filled.